Between Homogenisation and Vehicular Matching: A Diachronic Analysis of Language Representation in Multilingual Cinema - De Bonis, Giuseppe (Journal of Audiovisual Translation, 2025)
This paper examines the role of foreign languages in cinema, focusing on their narrative and cultural function in dramas, particularly within the subgenres of romance and war. Since the advent of sound in the 1930s, cinema has strived to realistically portray linguistic and cultural diversity, especially in the context of intercultural encounters. In romance and travel films, languages beyond the primary language often serve to bridge cultural gaps, explore diversity, and convey the complexity of cross-border relationships. Conversely, in war films, foreign languages frequently function as markers of the “Other,” representing opposing forces and intensifying conflict. This study analyses significant examples from both US and European cinema, spanning from the 1930s to the 2000s, and offers a diachronic exploration of how multilingualism contributes to narrative progression, emotional engagement, and the portrayal of cross-cultural dynamics. Framed by the representational mechanisms of vehicular matching and linguistic homogenisation (Sternberg, 1981; O’Sullivan, 2007, 2011), the analysis focuses on films that, while appearing to present a realistic use of more than one language, reveal a quantitatively reduced presence of secondary languages. The study also examines the approach followed in Italian dubbing, which mediates the multilingual dimension through strategies such as part-subtitling, contextual translation, and revoicing, ultimately underscoring the cultural and emotional significance of linguistic representation in cinema. Lay summary This study looks at how films use foreign languages to make their stories more engaging, especially in romance and war movies. Since the 1930s, filmmakers have included languages other than the main one spoken in the film to show cultural diversity and build connections between characters. In love stories and travel films, foreign languages help to overcome cultural differences and to celebrate relationships between people from different backgrounds. In contrast, war films often use foreign languages to highlight conflicts and emphasise the divide between opposing sides. The research examines some US and European films made between the 1930s and 2000s, showing how the use of multiple languages adds depth to the story, creates emotional moments, and portrays cultural exchanges. It also explores how the Italian dubbing of such films handles the presence of foreign languages in a film, using methods like adding subtitles to some parts or leaving foreign dialogue as it is. These choices highlight the important role that language plays in shaping both cinematic storytelling and viewers’ understanding of culture and identity.